CLASSROOM MANAGEMENT IN THE TEACHING AND LEARNING OF HISTORY - Handayani, Sri (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2013)
History education, including the teaching and learning of history, is a form of teaching and learning that is establishing national character values as to develop critical and chronological thinking as well as to acquire knowledge about the past in order to understand and explain the development and the changes in society as well as socio cultural diversity in order to find national identity among world society. The goals of the teaching and learning will be achieved if the student are well managed. As to manage teaching and learning in a proper way, educational management is required. Teaching and classroom management are a certain activities or process in managing cooperative group efforts in educational organization as to reach the goals effectively and efficiently. The functions of management includes: planning, organizing, actuating, controlling and evaluating. History education requires the functions in order to manage teaching and learning to be productive. Productivity is reflected from the effectivity and efficiency of learning.